1 - Covid-19, Pathogénicité des Logiques Nécropolitiques et Persistance de la Colonialité Économique en Afrique Sub-Saharienne: - Jacquineau Azétsop; Martin Ghislain Abéga (African Sociological Review, 2022)
More than a year after the appearance of covid-19, Africa is the continent least affected by this crisis for many reasons including the effectiveness of its pharmacopoeia and its health system trained, by experience, to manage epidemics of all kinds. The current pandemic is less a health crisis than an economic and financial crisis that reveals the politico-economic coloniality under which the African continent is bending. The covid-19 crisis has a revealing and “de- colonial” effect. It reveals on the one hand the fragility of African economies in the face of exogenous shocks and the limits of neoliberal policies incapable of providing effective solutions to global challenges and on the other hand, the affirmation of the unrecognized effectiveness of endogenous knowledge and the resurgence of pan-Africanist and sovereigntist discourses. For African countries, this crisis could serve as a springboard to reinvent themselves and reclaim their politico-economic emancipation based on endogenous forces and the pooling, at regional and continental level, of these same forces. The development of local resources, long neglected and despised, is an important condition for re-initiating the re-conquest of the political-economic and symbolic sovereignty of African countries.